Development of an Artificial Intelligence-Based Green Smart Manufacturing Framework for Sustainable Industrial Transformation - Mufidah Nurul Afiya (IHSA Institute, 2026)
Manufacturing industries are facing increasing pressure to enhance productivity and operational efficiency while simultaneously reducing environmental impacts and supporting sustainable development goals. In response to these challenges, Artificial Intelligence (AI) has emerged as a transformative technology capable of enabling intelligent, data-driven, and environmentally responsible manufacturing systems. This study aims to develop a Green Smart Manufacturing Framework based on Artificial Intelligence that integrates sustainability principles with smart manufacturing technologies to support sustainable industrial transformation. The framework was developed using the Design Science Research (DSR) methodology, which involved problem identification, literature analysis, framework design, development, and expert-based validation. The findings identified three core dimensions of Green Smart Manufacturing, namely Green Manufacturing, Smart Manufacturing, and AI Capability, which were integrated into a unified framework architecture. The study contributes to the existing body of knowledge by extending Green Manufacturing theory through the integration of Artificial Intelligence and sustainability concepts within a comprehensive smart manufacturing architecture.